КЕРУВАННЯ АВТОНОМНИМ АСИНХРОННИМ ГЕНЕРАТОРОМ З ВЕНТИЛЬНО-КОНДЕНСАТОРНОЮ СИСТЕМОЮ РЕГУЛЮВАННЯ РЕАКТИВНОЇ ПОТУЖНОСТІ НА ОСНОВІ БАГАТОМОДУЛЬНОГО ПЕРЕТВОРЮВАЧА - Мазуренко, Л.І.; Джура, О.В.; Шихненко, М.О.; Коротін, С.М. (Інститут електродинаміки НАН України, Київ, 2024)
The principles of multi-level output voltage control of an autonomous power supply system implemented on the basis of a three-phase constant speed self-excited induction generator with a regulated source of reactive power connected to the stator terminals and containing both a multi-modular electronic power converter and excitation capacitors are proposed. To regulate the voltage of the specified system, a stator voltage oriented vector control algorithm has been developed. Using the developed dynamic simulation model, numerical investigations of electromechanical processes in the system supplying RL-load of the local consumers were carried out to verify the effectiveness of the proposed principles of voltage control and the proposed vector control algorithm of the generator. The main advantages of applying multi-module electronic power converters in autonomous power supply systems using a self-excited induction generator with a short circuited rotor winding and an electronic power converter connected to the stator terminals for reactive power control are noted. References 10, figures 3, table 1.